Field-Based Evaluation of Insecticide Effectiveness on Megalurothrips usitatus in Guangdong, China: Implications for Pest Control Strategies - Zhengke Peng; Mengni Li; Chaosong Guo; Huixin Zheng; Mingyue Wu; Fei Yin; Yong Xiao; Huanhuan Wang; Xiangyi Kong; Myron P. Zalucki; Wen Xie; Zhenyu Li (Insects)
In southern China, cowpea production is severely threatened by Megalurothrips usitatus due to its fast-evolving resistance to insecticides. The toxicity monitoring of commonly used insecticides against field populations provides key information for the resistance management of pests. In this study, field populations of Megalurothrips usitatus were collected from three locations (QY, YF, MM) in Guangdong, and the sensitivity of these populations against insecticides was determined by using a thrips insecticides bioassay system (TIBS) method. The bioassay results indicated there were sensitivity variances to insecticides between these three field populations. Among these 10 insecticides, spinetoram and spinosad both showed high toxicity against all three field populations. In addition, broflanilide for QY, emamectin benzoate for YF, and emamectin benzoate and cyantraniliprole for MM were suggested as alternate insecticides to alleviate selective pressure from insecticides on field populations. In field experiments, the corrected control efficacy of cyantraniliprole and spinetoram against M. usitatus was over 75% at 7 dpa, which proved to be ideal insecticides for field application. These field-based results provide guidance for chemical control against thrips and can be valuable in proposing appropriate strategies for thrips resistance management.